Encapsulation of Olive Leaf Polyphenol-Rich Extract in Polymeric Micelles to Improve Its Intestinal Permeability - Maria Camilla Bergonzi; Chiara De Stefani; Marzia Vasarri; Emilija Ivanova Stojcheva; Alba María Ramos-Pineda; Francesco Baldi; Anna Rita Bilia; Donatella Degl’Innocenti (Nanomaterials, 2023)
In the present study, polymeric micelles were developed to improve the intestinal permeability of an extract of Olea europaea L. leaf with a high content of total polyphenols (49% w/w), with 41% w/w corresponding to the oleuropein amount. A pre-formulation study was conducted to obtain a stable formulation with a high loading capacity for extract. The freeze-drying process was considered to improve the stability of the formulation during storage. Micelles were characterized in terms of physical and chemical properties, encapsulation efficiency, stability, and in vitro release. The optimized system consisted of 15 mg/mL of extract, 20 mg/mL of Pluronic L121, 20 mg/mL of Pluronic F68, and 10 mg/mL of D-α-tocopheryl polyethylene glycol succinate (TPGS), with dimensions of 14.21 ± 0.14 nm, a polydisersity index (PdI) of 0.19 ± 0.05 and an encapsulation efficiency of 66.21 ± 1.11%. The influence of the micelles on polyphenol permeability was evaluated using both Parallel Artificial Membrane Permeability Assay (PAMPA) and the Caco-2 cell monolayer. In both assays, the polymeric micelles improved the permeation of polyphenols, as demonstrated by the increase in Pe and Papp values.